Gambaran Pelayanan Kader pada Program Bina Keluarga Balita (BKB) Permata Bunda di Desa Kolok Mudik Kecamatan Barangin Kota Sawahlunto - Ezzy Gusty Amelia; Syuraini Syuraini; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high participation of participants in participating in BKB activities, as seen from the number of participants who attend each month. This is allegedly due to good cadre service in providing each service to BKB participants. The purpose of this research is first to describe cadre work discipline in BKB program, secondly to describe cadre communication in BKB program, third to describe service facilities in BKB program in Kolok Mudik Village Barangin District, Sawahlunto City. This type of research is quantitative descriptive. The population in this study amounted to 87 BKB participants. The sample was taken 50% of the population totaling 44 people. The sampling technique in this study is cluster random sampling method. Data collection techniques used are questionnaires, while data analysis uses a percentage formula. The results showed that cadre service was very good according to BKB participants, this was seen from three aspects, including work discipline, communication, facilities. It is recommended to all those involved in the activities of the BKB Permata Bunda in Kolok Mudik Village, Barangin District, Sawahlunto City, to maintain the quality that has been carried out well. Keywords: Service, Cadre, BKB